Immunogenicity of HLA-DR1 Restricted Peptides Derived from Leishmania major gp63 Using FVB/N-DR1 Transgenic Mouse Model - H Rezvan (Iranian Journal of Parasitology, 2013)
Background: Leishmaniasis is a worldwide disease prevalent in tropical and sub- tropical countries. In the present study the immunogenicity of three human HLA-DR1 restricted peptides derived from L. major gp63 protein was evaluated using FVB/N-DR1 transgenic mouse model.